Metastatic Pattern Discriminates Survival Benefit of Type of Surgery in Patients With De Novo Stage IV Breast Cancer Based on SEER Database - Li, Kunlong; Zhou, Can; Yu, Yan; Niu, Ligang; Zhang, Wei; Wang, Bin; He, Jianjun; Ge, Guanqun (Frontiers in Surgery, 2021)
Background: The role of surgery and surgery type in de novo stage IV breast cancer (BC) is unclear. Methods: We carried out a retrospective cohort study that included the data of 4,108 individuals with de novo stage IV BC abstracted from SEER (Surveillance, Epidemiology, and End Results) data resource from 2010 to 2015. The patients were stratified into non-surgery group, breast-conserving (BCS) surgery group, and mastectomy group. IPTW was then used to balance clinicopathologic factors. Overall survival (OS), as well as the breast cancer-specific survival (BCSS) were assessed in the three groups using Kaplan-Meier analysis and COX model. Subgroups were stratified by metastatic sites for analysis. Results: Of the 4,108 patients, 48.5% received surgery and were stratified into the BCS group (574 cases) and mastectomy group (1,419 cases). After IPTW balance demographic and clinicopathologic factors, BCS and mastectomy groups had better OS (BCS group: HR, 0.61, 95% CI: 0.49-0.75; mastectomy group: HR, 0.7, 95% CI: 0.63-0.79) and BCSS (BCS group: HR, 0.6, 95% CI, 0.47-0.75; mastectomy group: HR, 0.71, 95% CI, 0.63-0.81) than the non-therapy group. Subgroup analyses revealed that BCS, rather than mastectomy, was linked to better OS (HR, 0.66; 95% CI: 0.48-0.91) and BCSS (HR, 0.63; 95% CI: 0.45-0.89) for patients with bone-only metastasis. For patients with viscera metastasis or bone+viscera metastases, BCS achieved similar OS (viscera metastasis: HR, 1.05, 95% CI: 0.74-1.48; bone+viscera metastases: HR, 1.01, 95% CI: 0.64-1.61) and BCSS (viscera metastasis: HR, 0.94, 95% CI: 0.64-1.38; bone+viscera metastases: 95% CI: 0.66-1.73; HR, 1.06) in contrast with mastectomy. Conclusions: Local surgery for patients with distant metastasis exhibited remarkable survival advantage in contrast with non-operative management. BCS may have more survival benefits for de novo stage IV BC patients with bone-only metastasis than other metastatic sites. Decisions on de novo stage IV BC primary surgery should be tailored to metastatic pattern.